The Complex Lives of Star Clusters - Stevenson, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
As with the author’s recent books Extreme Explosions and Under a Crimson Sun, the complex topic of star clusters is broken down and made accessible with clear links to other areas of astronomy in a language which the non-specialist can easily read and enjoy. The full range of a star cluster's lifespan is depicted, as both globular and open clusters are tracked from birth to eventual death. Why is it some are dense conglomerates of stars while others are looser associations? Are the young, brilliant clusters seen in neighboring galaxies such as the Large Magellanic Cloud, M33 or M82 analogous to the ancient globulars seen in the Milky Way? How will these clusters change as their stars wane and die? More interestingly, how does living in a dense star cluster affect the fates of the stars and any attendant planets that accompany them?   Star clusters form many of the most dazzling objects in the astronomers’ catalogs. Many amateur astronomers are interested in exploring how these objects are created and what it would be like to live among these objects. From the historical views of how star clusters came about to the most recent assumptions about how stars within these clusters evolve, different strands of science, from observation to theory, are woven together into a compelling investigation specifically targeted at amateur astronomers.
Initial Observations -- Formation of Stars and Clusters -- Globular Clusters as a Unique Case? -- The Death of Open Clusters -- The Evolution of Globular Clusters -- Complex Lives -- Planets in Clusters -- Milkomeda as a Last Hurrah for Star Formation in our Galaxy? -- Glossary -- Index.
Keywords: Astronomy; Astrophysics; Popular Science in Astronomy; Astronomy, Astrophysics and Cosmology